Obstetric Referrals to a Tertiary Teaching Hospital of Nepal - Maskey, S (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study was done to review the primary reasons and pattern of obstetric cases referred to Tribhuvan University Teaching Hospital, and to identify the clinical course, mode of management, maternal and perinatal outcomes. Methods: This prospective observational study reviewed 112 obstetric cases referred from various centers. Thorough history was taken; complete physical and obstetric examination and relevant investigations were done. Management of the patient, clinical course, mode of delivery, both maternal and perinatal outcomes were documented. Results: Most common diagnosis at referral was medical disorders complicating pregnancy (38%) among which cardiac disease accounted for 20%, followed by hypertensive disorder (17%). Unavailability of perinatal facility was the most frequent reason (24%) for referral. Twenty seven percent of the patients were in serious or critical condition on arrival, 52% patients required surgical intervention, 19% received intensive care management and there were mortalities of 2 women (1.8%). Total number of live births were 70 (62.5%) among which 28 (42%) required neonatal admission and 3 (4% of live birth) had early neonatal death. Conclusions: Wide spectrum of complicated obstetric cases were referred to this hospital. Unavailability of perinatal facility was the most common reason for referral followed by unavailability of physician. Most common diagnosis at the time of referral was medical disorders complicating pregnancy.